2015
DOI: 10.1093/infdis/jiv321
|View full text |Cite
|
Sign up to set email alerts
|

High Anti–Dengue Virus Activity of theOASGene Family Is Associated With Increased Severity of Dengue

Abstract: Dengue is a mosquito-borne viral disease that afflicts millions of individuals worldwide every year. Infection by any of the 4 dengue virus (DENV) serotypes can result in a spectrum of disease severity. We investigated the impact of variants of interferon-regulated innate immunity genes with a potent antiviral effect on the outcome of DENV infection. We compared the effect of OAS gene family variants on 2 DENV serotypes in cell culture. While both OAS1-p42 and p46 showed antiviral activity against DENV-2, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
(60 reference statements)
1
27
1
Order By: Relevance
“…The iDENV group was subjected to 60 C heat-inactivated DENV for 30 min. The numbers of mice in each group ranged from 6 to 8. these data supported our findings (Simon-Loriere et al, 2015). However, DENV infection results in the inhibition of antiviral IFN signaling, which is attributable to DENV NS2B/NS3 proteasemediated cleavage of human mediator of IRF3 activation (MITA) (Yu et al, 2012), NS4A-mediated inhibition of TBK1/IRF3 phosphorylation (Dalrymple et al, 2015), and NS5 replicase-mediated inhibition of STAT2 expression (Morrison et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The iDENV group was subjected to 60 C heat-inactivated DENV for 30 min. The numbers of mice in each group ranged from 6 to 8. these data supported our findings (Simon-Loriere et al, 2015). However, DENV infection results in the inhibition of antiviral IFN signaling, which is attributable to DENV NS2B/NS3 proteasemediated cleavage of human mediator of IRF3 activation (MITA) (Yu et al, 2012), NS4A-mediated inhibition of TBK1/IRF3 phosphorylation (Dalrymple et al, 2015), and NS5 replicase-mediated inhibition of STAT2 expression (Morrison et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Clinically, low levels of type I IFN have been observed in patients with severe dengue-associated disease, revealing that the IFN system plays an important role in preventing DENV infection and pathogenesis (Jones et al, 2005;Ubol et al, 2008). Several reports demonstrated that IFN-stimulated genes and proteins could inhibit DENV replication, such as IFN-induced transmembrane protein 2 and 3 (IFITM2 and IFITM3), doublestranded RNA-dependent protein kinase, and 2 0 , 5 0 -oligoadenylate synthetase/RNase L (OAS) (Jiang et al, 2010;Simon-Loriere et al, 2015); thus, boosting the IFN-mediated antiviral response might represent a potent strategy against DENV infection. Tripterygium wilfordii (lei gong teng; Thunder of God Vine), a member of the Celastraceae family, is a medicinal plant used to treat a range of illnesses including inflammation, swelling, fever, sores, and pain, and it has been used in India, Japan, China, Korea, and other Asian countries for some time (Ju et al, 2015;Lee et al, 2015b;Youn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To escape host antiviral immune responses and facilitate virus replication, viral proteins would interfere with antiviral IFN responses for an efficient virus production, such as human papilloma virus (HPV), human parainfluenza virus 2 (HPIV2), and West Nile virus (WNV)282930. Current studies have demonstrated that enhanced ISG expression sufficiently suppresses DENV replication through IFN-induced transmembrane protein 2 and 3 (IFITM2 and 3), PKR, and OAS genes712. It would be noteworthy to further clarify how schisandrin A interrupts DENV protein-suppressed antiviral IFN pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, phosphorylated STAT1–STAT2 heterodimer binds to IFN-regulated gene 9 and form a transcriptional complex of IFN-stimulated gene factor 3 (ISGF3). ISGF3 then translocates into the nucleus and binds to the IFN- stimulated response element (ISRE) to trigger the expression of several antiviral IFN-stimulated genes (ISGs), including 2′-5′-oligoadenylate synthetase 1 (OAS1), OAS2, OAS3, and protein kinase R (PKR), which ultimately collapses different stages of virus replication91112. In case of DENV infection, NS2B/3 protease subverts IFN activation by targeting MITA protein, NS4B interferes IFN pathway by blocking STAT1 phosphorylation, and NS5 blocks JAK-STAT2 pathway by degradation of STAT2 protein to prevent antiviral gene expression91314.…”
mentioning
confidence: 99%
“…OAS3 (rs2285932-rs2072136) haplotype and C-G haplotype might be associated with reduced risk of Dengue Hemorrhagic Fever, while the G-G haplotype of OAS2 gene (rs15895 and rs1732778) may be associated with increased risk of symptomatic dengue requiring hospitalization . A recent study has reported that OAS gene cluster variants that contributed to higher OAS activity were associated with dengue disease severity (Simon-Loriere et al, 2015).…”
Section: Discussionmentioning
confidence: 99%